Handbook of ethnography - Atkinson, Paul, 1947- (London : SAGE, 2001)
This handbook provides a critical guide to the past, present and future of ethnography.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Ethnology -- Methodology